Aspek-Aspek Dalam Perbankan Syariah Dan Implementasinya - Dela sari; Erika Anjung Fatayanti; Redho Arifin Redho arifin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
There are at least four aspects of Islamic banking: meeting the needs of people who cannot accept the concept of interest, establishing a dual banking system in Indonesia, lowering the systemic risk of financial system failure in Indonesia, and encouraging the role of banking in driving the real sector while limiting speculative or unproductive activities. As a result, the primary goal of Islamic banking is to eliminate interest from all transactions and achieve a fair distribution of income and wealth, justice, the foundation of Islamic financial mechanisms will be able to realize more fair and transparent economic activities, benefits, and balance. As a result, sharia values must be examined from both a micro and macro level.